The Gut Microbiome Signatures Discriminate Healthy From Pulmonary Tuberculosis Patients - Hu, Yongfei; Feng, Yuqing; Wu, Jiannan; Liu, Fei; Zhang, Zhiguo; Hao, Yanan; Liang, Shihao; Li, Boxing; Li, Jing; Lv, Na; Xu, Yuhui; Zhu, Baoli; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Cross talk occurs between the human gut and the lung through a gut-lung axis involving the gut microbiota. However, the signatures of the human gut microbiota after active Mycobacterium tuberculosis infection have not been fully understood. Here, we investigated changes in the gut microbiota in tuberculosis (TB) patients by shotgun sequencing the gut microbiomes of 31 healthy controls and 46 patients. We observed a dramatic changes in gut microbiota in tuberculosis patients as reflected by significant decreases in species number and microbial diversity. The gut microbiota of TB patients were mostly featured by the striking decrease of short-chain fatty acids (SCFAs)-producingbacteria as well as associated metabolic pathways. A classification model based on the abundance of three species, Haemophilus parainfluenzae, Roseburia inulinivorans, and Roseburia hominis, performed well for discriminating between healthy and diseased patients. Additionally, the healthy and diseased states can be distinguished by SNPs in the species of B. vulgatus. We present a comprehensive profile of changes in the microbiota in clinical TB patients. Our findings will shed light on the design of future diagnoses and treatments for M. tuberculosis infections.